(untitled) (Revista Apotheke, 2021)
Maxwell Alexandre was born, lives, and works in Rio de Janeiro, a resident of Rocinha, one of the biggest slums of Latin America. This paper pursues the relation of Maxwell Alexandre’s paintings, from his relationship with the colors. Part of that concernment is due to one of the artist’ series called “Pardo é paper”. Maxwell presents a homonym exhibition in Lyon, Rio de Janeiro, and Porto Alegre. In a few years of production, the artist turns one of the most important references to Brazilian art and, mainly, makes part in the young Afro-descendant scene of art. Ethnic racial relations, black people empowerment, hip hop music universe, there are many possible connections between Maxwell Alexandre’s production and the recent production of the art, music, and society with the markers of race and class. The color dialogues with publicity elements and regulatory institutions, as the city police and the public school, as well as the Rio de Janeiro’s flag. In another way, the paper pursues to discuss the racial theories and the possibility of an Afro-descendant artist to deal with an element, the color, so related to a racist and excluding art system.